DETERMINAN KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR ASURANSI DI BURSA EFEK INDONESIA - Evriyanna Nur Maidah (2022)
The purpose of this study was to determine factors such as Claim Expenses, Own Retention, Risk Based Capital, Gross Domestic Product, Interest Rates, and Inflation on the Financial Performance of Insurance Sub-Sector Companies listed on the IDX. The population used in this study are insurance sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2021 period. By using the full sampling method or saturated sample so that the entire population in this study was used as the research sample, so that there were 18 insurance companies used as samples. The data analysis technique used in this study was panel data regression analysis using E-Views 12 software. It was found that the most suitable method used in this study was the Random Effect Model (REM). The results of this study indicate that partially only the Claim Expense variable has an effect on Financial Performance, while partially for the Own Retention, Risk Based Capital, Gross Domestic Product, Interest Rates, and Inflation variables have no effect on Financial Performance.